Ekonomska upravičenost uporabe metod digitalne forenzike - Selinšek, Liljana (LeXonomica, 2020)
Economic justification of use of digital forensic methods. The author is trying to connect the field of law and economics with the usage of digital forensic methods that are increasingly important evidence means in modern information society for proving of different criminal offences’ elements as well as other important facts in legal proceedings. The basis of the article is the (hypo)thesis that digital forensic methods are proper evidence means only in cases where expected benefit from evidences collected with this methods is higher than the costs of digital forensic investigation. The author is pointing out also the fact that economic views of digital forensics are of complex nature because they interfere with the battle between commercial and open source tools for digital forensic investigations where many interests collide: those of technological companies that develop forensic software, of police, jurisdiction and consumers.Povzetek. Članek skuša povezati področje ekonomske analize prava z uporabo digitalnih forenzičnih metod, ki so v sodobni informacijski družbi čedalje bolj uporabno sredstvo za dokazovanje znakov različnih kaznivih dejanj, pa tudi drugih pravno pomembnih dejstev. Avtorica izhaja iz temeljne hipoteze, da je dokazovanje z metodami digitalne forenzike primerno uporabiti le, kadar pričakovana korist od tako zbranih dokazov presega stroške digitalne forenzične preiskave. Hkrati opozarja, da so stroškovni vidiki digitalne forenzike izjemno kompleksni, saj segajo na področje bitke med komercialnimi in odprtokodnimi orodji za digitalne forenzične preiskave, kjer trčijo interesi tehnoloških podjetij, ki razvijajo forenzično programsko opremo, interesi policije in pravosodja ter interesi potrošnikov.
Keywords: digital forensics; criminal proceedings; electronic evidences; law and economics